Incidence of corporate social responsibility practices on the cost of equity: evidence from Colombian companies (2020)
This study analyzes the effect of corporate social responsibility (CSR) practices on the cost of equity, for Colombian companies that are listed on the Colombian Stock Exchange (BVC, Bolsa de Valores de Colombia) and have produced sustainability reports through the Global Reporting Initiative (GRI), for the period 2012-2016. Using the panel data model for thirty-one companies, it was found that companies which implemented CSR practices and included them on their corporate reports reduced their cost of capital. Furthermore, it was also found that the length of the corporate report, and how unbiased it is, both reduce the cost of equity.